Association of midlife body composition with old-age health-related quality of life, mortality, and reaching 90 years of age: a 32-year follow-up of a male cohort. Issue 5 (25th August 2020) - Jyväkorpi, Satu K; Urtamo, Annele; Kivimäki, Mika; Salomaa, Veikko; Strandberg, Timo E
ABSTRACT: Background: Overweight and obesity increase the risk of morbidity and mortality. The relations between body composition at midlife, health-related quality of life (HRQoL) in old age, and longevity are, however, less studied. Objectives: We examined the association of midlife body composition with successful aging, defined as high HRQoL and reaching 90 y of age, during 32 y follow-up. Methods: Participants were 1354 men from the Helsinki Businessmen Study, born 1919–1934. In 1985/1986 (mean age: 60 y) various health measurements were performed. Percentages of body fat (BF) and skeletal muscle mass (SM) were calculated using validated formulas (including waist and hip circumferences, weight, and age) and divided into quartiles. In 2000 and 2007 (mean ages: 74 and 80 y, respectively), HRQoL was assessed using RAND-36/Short Form-36 scales. Mortality was retrieved from registers through 2018, and longevity determined by calculating the proportion of participants reaching 90 y. Logistic regression was used to assess ORs with 95% CIs. Results: Higher SM% at midlife in 1985/1986 was associated ( P  < 0.05) with higher scores in the RAND-36 scales of physical functioning, role limitations caused by physical health problems, vitality, social functioning, and general health in old age in 2000. In 2007 only the association with physical domain (physical functioning, role limitations caused by physical health problems) remained statistically significant ( P  < 0.01). BF% quartiles in 1985/1986 were inversely associated with several RAND-36 scales in 2000 and 2007. During the 32-y follow-up, 982 participants died and 281 reached 90 y of age. Being in the highest SM% quartile at midlife increased (adjusted OR: 2.32; 95% CI: 1.53, 3.53; lowest SM% quartile as reference) and being in the highest BF% quartile decreased (OR: 0.43; 95% CI: 0.28, 0.66; lowest BF% quartile as reference) the odds of reaching 90 y. Conclusions: Desirable body composition in terms of both fat and skeletal muscle mass at midlife was associated with successful aging in men. This trial was registered at clinicaltrials.gov as NCT02526082.